1989
DOI: 10.1002/bjs.1800760113
|View full text |Cite
|
Sign up to set email alerts
|

111In-labelled leucocyte imaging in vascular graft infection

Abstract: Twelve patients with a clinical diagnosis of possible vascular graft infection have been studied over the last 3 years. All patients had their leucocytes labelled with indium-111 and gamma-camera imaging after 24 and 48 h. Subsequent management was according to established surgical techniques. Eight patients proved to have vascular graft infection and indium uptake was seen along the length of the graft in six. Two patients with open wound infections and synthetic grafts had localized uptake only on leucocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…1 It is reasonable to consider CT imaging as the initial imaging procedure in patients with suspected intraabdominal VGI. In the absence of recent manipulations, 1,[33][34][35] Several studies have reported that PET/CT is useful for the diagnosis of intra-abdominal VGI. 1,[28][29][30][31][32][42][43][44][45][46] Three recent studies summarized the role of PET/CT for the diagnosis of VGI.…”
Section: Intra-abdominal Vgimentioning
confidence: 99%
“…1 It is reasonable to consider CT imaging as the initial imaging procedure in patients with suspected intraabdominal VGI. In the absence of recent manipulations, 1,[33][34][35] Several studies have reported that PET/CT is useful for the diagnosis of intra-abdominal VGI. 1,[28][29][30][31][32][42][43][44][45][46] Three recent studies summarized the role of PET/CT for the diagnosis of VGI.…”
Section: Intra-abdominal Vgimentioning
confidence: 99%